A unique Early Iron Age brooch from Somló Hill - Soós, Bence; Lukács, Balázs; Líbor, Csilla (Communicationes Archaeologicae Hungariae, 2024)
The aim of this paper is to present an important addition to our knowledge about the Early Iron Age of Somló Hill. In early February 2023, during a metal detector survey of the hill volunteer detectorist Roland Moklovsky found a bronze brooch decorated with a small ornithoid figurine. Although the item is a stray find, its typological relations, and technical characteristics make it one of the most significant archaeological discoveries on the hill.